Pemakaian Metode Numerik Pada Sirkulasi Udara di Sekitar Bangunan Tradisional Bali - I Gusti Bagus Wijaya Kusuma (Jurnal Matematika & Sains, 2002)
The airflow patterns around traditional Balinese buildings cannot be estimated by experiment method nor using modern buildings, since the position and the function of a building on a cluster of traditional Balinese buildings are linked each other. It is not correct if the investigation uses an isolated building and symmetrical method in order to understand the airflow patterns of all buildings. Numerical method based on finite volume is used in this simulation since it gives quicker analyses and capable of delivering more detailed and comprehensive information about the flow structure around 3-dimension buildings. Results show that numerical method gives more accurate prediction of airflow patterns around traditional buildings.